Composite material for high-temperature thermal evaporation of tellurium and preparation method thereof
By using composite materials prepared by tellurium powder, bismuth particles and cerium particles, combined with the use of silicon carbide nanowires, the problem of excessively rapid evaporation of tellurium in high-temperature thermal evaporation is solved, and the stability of film components and high-temperature performance is improved.
Patent Information
- Application Number
- CN202510368512.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
During the high-temperature thermal evaporation process, the saturated vapor pressure of pure tellurium is high, causing tellurium to evaporate too quickly, affecting the quality and performance of the film. The high-temperature degassing process will cause tellurium to evaporate, increasing production costs and pollution risks.
Using a composite material with tellurium powder, bismuth particles and metal cerium particles as raw materials, a composite material including at least Bi2Te3 phase and Te-rich phase is obtained by smelting, the evaporation of tellurium is controlled, the evaporation of bismuth is suppressed, and the high-temperature creep resistance is improved through silicon carbide nanowires.
The stable evaporation of tellurium is achieved, ensuring the stability of the film composition, improving the thermal stability and creep resistance of the material, extending the service life, reducing production costs, and improving the purity and uniformity of the film.
Smart Images

Figure CN119876859A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of vacuum evaporation, and specifically relates to a composite material for high-temperature thermal evaporation of tellurium and a preparation method thereof. The composite material can be used for high-temperature evaporation coating of a tellurium layer, can significantly reduce the saturated vapor pressure of tellurium in an evaporation source, inhibit excessive evaporation of tellurium, avoid contaminating a chamber and affecting product device performance. Background Art
[0002] High-temperature thermal evaporation, also known as thermal evaporation, is a common method for preparing film layers. It has important applications in semiconductors, optoelectronics, thermoelectrics and other fields. It is to evaporate the source material into gaseous particles by heating, and use carrier gas to transport the generated source material vapor to a low-temperature zone or to evaporate the gaseous particles upward through a high-temperature environment, and then reach the substrate (such as glass, silicon wafer), and deposit, nucleate and grow in a specific temperature zone. After a certain reaction time, the final product material is obtained. This is a physical vapor deposition method. Compared with other film-forming or coating methods such as chemical vapor deposition, sputtering coating, electroplating, etc., it has the following advantages: high film quality, high product purity, relatively few impurities and defects; good uniformity, the raw materials can be uniformly deposited by controlling the parameters, suitable for large-area base coating; high temperature environment is conducive to crystal growth and good crystallization performance; high coating efficiency, can achieve a faster coating speed, can reach the required film thickness in a shorter time, and high production efficiency. The process of thermal evaporation is relatively simple, and the equipment composition and operation process are not complicated. The main equipment includes vacuum coating chamber, evaporation source, heating device, vacuum system, etc. The operator can accurately control the growth of the thin film by controlling the heating power of the evaporation source, coating time, vacuum degree and other parameters. It is easy to realize automated operation, improve production efficiency and the stability of coating quality, and is suitable for large-scale industrial production.
[0003] Tellurium (Te) is a well-known basic material for preparing compound semiconductor materials. It has excellent optoelectronic properties, high carrier mobility, extremely low room temperature lattice thermal conductivity and excellent environmental stability. The smaller band gap makes it possible to have wide spectrum detection capabilities, and the richer optoelectronic properties make it have diverse applications. For example, cadmium telluride can be used to make light-emitting diodes, radiation detectors and solar cells; mercury-cadmium telluride alloy is the best material for infrared emitters and detectors; tellurium-bismuth-selenium-antimony alloy is an important thermoelectric material that can be used for power generation and cooling, such as for cooling of civilian products such as water dispensers, refrigerators, and air conditioners. It can also be used in space power systems, aerospace, high-altitude weather recording instruments, military radar coolers and submarine air conditioning devices. However, the purity of tellurium used to prepare the above materials must reach 4N or above to meet the raw material requirements, otherwise it will directly affect the performance and effect of the device. Therefore, in the application of tellurium, special attention is paid to the influence of impurities in the system. The melting point of tellurium is 450℃, and low-temperature growth can be achieved. Common methods for preparing tellurium thin films include thermal evaporation and magnetron sputtering. When pure tellurium is used as an evaporation source, there are strict restrictions on the temperature when preparing a tellurium layer at high temperature. Pure tellurium is prone to uneven evaporation at high temperatures, and may be accompanied by co-evaporation of impurity elements, resulting in unstable film composition and reduced performance. At the same time, due to the high saturated vapor pressure of pure tellurium, it can evaporate significantly when the temperature is higher than 200°C, resulting in its evaporation rate being too fast at high temperatures, affecting the reaction or the formation of tellurium film; at the same time, high-temperature degassing treatment (usually above 300°C) is often required before high-temperature thermal evaporation reactions, and this process will cause a large amount of tellurium to volatilize, which on the one hand wastes raw materials and increases production costs, and on the other hand will pollute the chamber and affect the quality of the film. For example, CN113241298A discloses a tellurium semiconductor film and a preparation method thereof, wherein the growth direction of the grains in contact with the substrate in the tellurium semiconductor film is parallel to the substrate, and the preparation method comprises: heating a solid-phase Te source placed in the heating zone of a vapor transport deposition tube under the condition of 0.003 to 25 torr to obtain gaseous Te; depositing the gaseous Te on a substrate located in the non-heating zone of the vapor transport deposition tube to obtain the tellurium semiconductor film. CN113517371A discloses a blackbody-sensitive room-temperature low-dimensional tellurium infrared photodetector, wherein a chemical vapor deposition method is used to grow and prepare low-dimensional Te nanowires and nanosheet materials on a Si substrate, and a physical transfer method is used to transfer the low-dimensional Te nanowires or nanosheet semiconductors 3 to the surface of an oxide layer 2, wherein SnTe2 powder is first placed on a ceramic boat and placed in the center of a quartz tube, and a tubular furnace outside the quartz tube can heat the system. The Si wafer is placed flat on the quartz boat and placed together in the downstream of the quartz tube airflow 15 cm away from the powder. Vacuum to 1×10 -1Pa, during the reaction process, the system maintains a flow rate of 100sccm of argon as a carrier gas, heating from room temperature to 650°C, the gas pressure is maintained at 1000Pa, and then kept warm for 30 minutes. After the experiment is completed, the heating is stopped and the carrier gas is continuously introduced, and the reaction tube is allowed to cool naturally to room temperature. Finally, the grown nanowires or nanosheets are physically transferred to a p-type silicon substrate with a SiO2 oxide layer mark. However, the equipment required for chemical vapor deposition is large in size, complex in operation, has high vacuum requirements, and the uniformity of the resulting Te film is poor. When using a pure tellurium source, its evaporation rate is difficult to accurately control. If the evaporation rate is too fast, the tellurium atoms will be deposited unevenly on the substrate surface, affecting the quality and performance of the tellurium film; if the evaporation rate is too slow, the production efficiency will be reduced and the preparation cost will be increased. In addition, tellurium is easy to react with oxygen in the air at high temperature. When using pure tellurium target for high-temperature thermal evaporation, if the vacuum environment is not ideal, the tellurium target is easily oxidized, which will not only affect the service life of the target, but also cause oxide impurities to be mixed into the evaporated tellurium film, reducing the purity and performance of the tellurium film. Although the method of using tellurium alloy for high-temperature evaporation can reduce the saturated vapor pressure of tellurium to a certain extent and achieve the stable existence of tellurium in the system during the high-temperature degassing stage, the current tellurium alloy system is relatively complex and does not effectively balance the vapor pressure and inhibit tellurium evaporation. Alloys with coarse grains or uneven phase distribution are prone to component segregation during the evaporation process, reducing the uniformity of the film and introducing impurities in the system due to the synchronous evaporation of alloy elements, affecting product quality.
[0004] In order to solve the above problems, the prior art often improves the thermal stability, anti-evaporation performance and microstructure of the material by doping other metals or adding reinforcing phases. However, these methods often have problems such as component segregation, poor interface bonding or complex processes, and it is difficult to meet the needs of high-performance thermal evaporation materials. Based on this, it is necessary to provide a composite material that can be used for high-temperature thermal evaporation of tellurium, which is used to prepare a composite material that can be used stably for a long time in high-temperature evaporation of tellurium, so that it can stably evaporate to prepare tellurium products without affecting product quality due to high-temperature degassing. Summary of the invention
[0005] In order to solve the defects in the prior art, the present invention provides a composite material for high-temperature thermal evaporation of tellurium and a preparation method thereof. The composite material is obtained by smelting tellurium powder, bismuth particles and metal cerium particles as raw materials, and includes at least a Bi2Te3 phase and a Te-rich phase. The raw materials contain the following components by mass fraction: tellurium powder (Te): 70%~74%; bismuth particles (Bi): 25%~29%; metal cerium particles (Ce): 0.5%~1%; silicon carbide nanowires: 0~0.5%. The composite material of the present invention can control the evaporation amount of tellurium, ensure the stability of the film composition, less tellurium evaporates in the high-temperature degassing stage at the early stage of thermal evaporation, and can also inhibit the evaporation of bismuth under high-temperature conditions. The material composition has a small deviation, the product purity is high, and the composition is stable; in addition, the thermal stability and creep resistance of the material can be improved, and the evaporation source can maintain stable performance after a long-term thermal cycle and has a long service life; the prepared composite material can prevent tellurium from evaporating at 200°C, and tellurium can be evaporated at about 350°C, and the bismuth element does not evaporate with the evaporation of tellurium, and will not pollute the device or the evaporation chamber.
[0006] To achieve the above-mentioned object of the present invention, the present invention provides a composite material for high-temperature thermal evaporation of tellurium, the composite material is obtained by smelting tellurium powder, bismuth particles and metal cerium particles as raw materials, and the composite material at least includes Bi2Te3 phase and Te-rich phase. The composite material selects metal bismuth and cerium with lower saturated vapor pressure to form an alloy with tellurium, Bi2Te3 has high thermal stability, the composite material needs to be much higher than the degassing temperature to evaporate and release tellurium, and the alloyed bismuth and cerium will not evaporate during the evaporation process, and the product purity is high.
[0007] Furthermore, the purity of the tellurium powder, bismuth particles and metal cerium particles is 4N or above. The use of raw materials with such purity can avoid the influence of impurities on material properties and improve the purity and uniformity of the final product.
[0008] Furthermore, the raw materials also include silicon carbide nanowires, the diameter of which is 5-50 nm and the length of which is 0.1-20 μm. The addition of silicon carbide nanowires can be distributed along the crystal boundaries of Bi2Te3, can pin the crystal boundaries, inhibit the lattice distortion of Bi2Te3 above 600°C, enhance the high-temperature creep resistance and high-temperature mechanical properties of the composite material, and extend the service life of the composite material.
[0009] Furthermore, the raw materials include the following components by mass fraction: tellurium powder (Te): 70%~74%; bismuth particles (Bi): 25%~29%; metal cerium particles (Ce): 0.5%~1%; silicon carbide nanowires: 0~0.5%.
[0010] Furthermore, the smelting is specifically as follows: weighing the raw materials, mixing the weighed bismuth particles, metal cerium particles, silicon carbide nanowires and 90% by weight of tellurium powder, placing the mixture in a vacuum melting furnace, maintaining the vacuum degree at 0.01~100Pa, and smelting at 620°C for 0.5~2h; then adopting a balanced solidification process, maintaining the solidification rate at 0.05K / s to room temperature to obtain an alloy; taking out the alloy and crushing it into 100~300 mesh powders, adding the remaining tellurium powder and placing it in a vacuum melting furnace, maintaining the vacuum degree at 0.01~100Pa, and smelting at 600°C for 1~2h; then adopting a balanced solidification process, maintaining the solidification rate at 0.05K / s to room temperature to obtain a composite material. The present invention adopts a balanced solidification process and secondary smelting to refine the grains, thereby improving the thermal stability of the material and the uniformity of evaporation. At the same time, a specific solidification rate is selected through a large number of experiments, which can effectively avoid component segregation caused by rapid cooling. The two smeltings can effectively refine the grains, reduce internal defects, and effectively reduce the possibility of internal pores during the smelting process.
[0011] Furthermore, the smelting temperature is programmed temperature rise, specifically: rising from room temperature to 400°C at a rate of 10°C / min, and then rising to the target temperature at a rate of 5°C / min.
[0012] Furthermore, the composite material is composed of Bi2Te3 phase and Te-rich phase, and the average particle size is 1-10 μm. Due to the low content of metal cerium, no obvious special crystal phase is present, and the material as a whole has good density and uniformity.
[0013] Furthermore, when the composite material is used for thermal evaporation, no Te or Bi evaporates below 200°C, and during the degassing treatment at 300°C, there is no splashing or holes on the material surface. At 350°C, tellurium begins to evaporate in a controllable manner, with an initial evaporation amount of less than 0.1wt%, while bismuth remains in a solid state and no evaporation occurs at 350°C. This shows that the composite material has good thermal stability.
[0014] Another object of the present invention is to provide a method for preparing a composite material for high-temperature thermal evaporation of tellurium, wherein the composite material uses raw materials comprising the following components by mass fraction: tellurium powder (Te): 70% to 74%; bismuth particles (Bi): 25% to 29%; metal cerium particles (Ce): 0.5% to 1%; silicon carbide nanowires: 0 to 0.5%. The preparation method comprises the following steps: 1) Weighing raw materials, mixing weighed bismuth particles, metal cerium particles, silicon carbide nanowires and 90% by weight of tellurium powder, placing in a vacuum melting furnace, maintaining a vacuum degree of 0.01-100 Pa, melting at 620° C. for 0.5-2 h; maintaining a solidification rate of 0.05 K / s, and cooling to room temperature for equilibrium solidification to obtain an alloy; 2) The alloy is taken out and crushed into 100-300 mesh to obtain powder, the remaining tellurium powder is added thereto, and the alloy is placed in a vacuum melting furnace, the vacuum degree is maintained at 0.01-100 Pa, and the alloy is melted at 600°C for 1-2 hours; the solidification rate is maintained at 0.05 K / s and the alloy is cooled to room temperature for equilibrium solidification to obtain a composite material.
[0015] Furthermore, the smelting temperature is programmed temperature rise, specifically: rising from room temperature to 400°C at a rate of 10°C / min, and then rising to the target temperature at a rate of 5°C / min.
[0016] The above preparation method can obtain a composite material with excellent high-temperature mechanical properties and high-temperature creep resistance, and the grain size is relatively uniform, which reduces component segregation and internal defects, improves the density of the material, and meets the requirements of component control during the evaporation process while ensuring the thermal stability of the material.
[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: 1. By setting a specific raw material system, the Bi2Te3 phase and the Te-rich phase in the composite material produce a synergistic effect. The thermally stable Bi2Te3 phase can effectively inhibit the evaporation behavior of bismuth at high temperature, and there is no bismuth evaporation at 350°C; the tellurium evaporation amount is optimized, and the presence of the Te-rich phase ensures the effective evaporation of tellurium, thereby achieving the stability and controllability of the film composition; the composite material has high thermal stability, which can realize high-temperature thermal evaporation of tellurium, avoiding the composition deviation and product contamination problems caused by high temperature in traditional materials.
[0018] 2. By introducing metal bismuth and cerium to form an alloy with tellurium, the saturated vapor pressure of tellurium is effectively reduced, ensuring that no unnecessary elements are introduced by evaporation under high temperature conditions, and the product composition is stable; avoiding the common component segregation problem in traditional materials, ensuring the purity and uniformity of the evaporated film, and the product quality is high.
[0019] 3. The composite material has a long service life. The introduction of silicon carbide nanowires can pin the grain boundaries and inhibit lattice distortion at high temperatures, significantly enhancing the high-temperature creep resistance of the composite material, allowing the composite material to maintain stable performance after long-term thermal cycles; specific preparation processes can also improve the microstructure, improve the density and uniformity of the material, reduce internal defects, and significantly extend the service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD pattern of the composite material prepared in Example 1 of the present invention; Figure 2 This is the SEM spectrum of the composite material prepared in Example 1 of the present invention; Figure 3The XRD spectrum of the thermally evaporated tellurium film of Example 1 of the present invention; Figure 4 This is the Raman spectrum of the thermally evaporated tellurium film according to Example 1 of the present invention. DETAILED DESCRIPTION
[0021] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0022] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0023] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0024] Example 1 A composite material for high-temperature thermal evaporation of tellurium is prepared from the following raw materials, wherein the raw materials include the following components by mass fraction: tellurium powder (Te): 70%; bismuth particles (Bi): 29%; metal cerium particles (Ce): 1%. The purity of tellurium powder, bismuth particles and metal cerium particles is 4N. The preparation method of the composite material is as follows: 1) Weigh the raw materials, mix 145g of bismuth particles, 5g of metal cerium particles and 315g of tellurium powder, place them in a vacuum melting furnace, maintain the vacuum degree at 100Pa, and melt them at 620℃ for 2h; maintain the solidification rate at 0.05K / s and cool them to room temperature for equilibrium solidification to obtain the alloy; the melting adopts programmed temperature increase, first at a rate of 10℃ / min from room temperature to 400℃, and then at a rate of 5℃ / min to 620℃; 2) The alloy was taken out and crushed into 100 mesh to obtain a powder, 35 g of tellurium powder was added thereto, and the powder was placed in a vacuum melting furnace, the vacuum degree was maintained at 50 Pa, and the powder was melted at 600 °C for 2 h. The melting temperature was programmed, first from room temperature to 400 °C at a rate of 10 °C / min, and then to 600 °C at a rate of 5 °C / min; the solidification rate was maintained at 0.05 K / s and the composite material was obtained by equilibrium solidification cooling to room temperature.
[0025] The composite material was tested. Figure 1 The XRD spectrum of the composite material shows that the composite material has two different phases, which correspond to Bi2Te3 phase and trigonal Te phase respectively. Due to the small amount of cerium, XRD does not show obvious diffraction peaks of metal cerium or cerium alloy. It can be seen from the figure that the half-width of the diffraction peak is very small, and no impurity peak appears, indicating that the composite material has good crystallinity. The composite material is composed of Bi2Te3 phase and trigonal Te phase, without other impurity peaks. The composite material was tested by SEM, such as Figure 2 It can be seen that the composite material particles are evenly distributed, have good crystallinity, no voids on the surface, and an average particle size of 1~5μm. The composite material is used as a thermal evaporation tellurium source to prepare a tellurium film by thermal evaporation. The composite material is added to the device, sealed and vented, and then heated to 300℃ for further degassing. After that, it is evaporated at 400℃ for a period of time to obtain a film layer sample. The sample is tested by XRD and Raman spectroscopy. Figure 3 The XRD spectrum shows that the sample is Te pure phase, with high diffraction peak intensity and good crystallization. Figure 4 The sharp Raman peaks in the Raman spectrum also confirm the high quality of the prepared tellurium film. At the same time, the prepared composite material was subjected to thermogravimetric analysis, which showed that there was no weight loss below 200°C, the evaporation of Te was about 0.09 wt% at 350°C, and there was no weight loss of Bi. After long-term high-temperature use, the particles on the surface of the material became loose and occasionally debris appeared. It can be seen that the lattice of the material is easily distorted in a long-term high-temperature environment, and the high-temperature creep resistance of the material is general.
[0026] Example 2 A composite material for high-temperature thermal evaporation of tellurium is prepared from the following raw materials, wherein the raw materials include the following components by mass fraction: tellurium powder (Te): 74%; bismuth particles (Bi): 25%; metal cerium particles (Ce): 0.5%; silicon carbide nanowires: 0.5%. The purity of tellurium powder, bismuth particles and metal cerium particles is 99.995%, the diameter of silicon carbide nanowires is 5-20nm, and the length is 0.1-5μm. The preparation method of the composite material is as follows: 1) Weigh the raw materials, mix 125g of bismuth particles, 2.5g of metal cerium particles, 2.5g of silicon carbide nanowires and 333g of tellurium powder, place them in a vacuum melting furnace, maintain the vacuum degree at 10Pa, and melt at 620℃ for 0.5h; maintain the solidification rate at 0.05K / s and cool to room temperature for equilibrium solidification to obtain the alloy; the melting adopts programmed temperature rise, first at a rate of 10℃ / min from room temperature to 400℃, and then at a rate of 5℃ / min to 620℃; 2) The alloy was taken out and crushed into 300 mesh to obtain a powder, 37 g of tellurium powder was added thereto, and the powder was placed in a vacuum melting furnace, the vacuum degree was maintained at 0.01 Pa, and the powder was melted at 600 °C for 1 h. The melting temperature was programmed, first from room temperature to 400 °C at a rate of 10 °C / min, and then to 600 °C at a rate of 5 °C / min; the solidification rate was maintained at 0.05 K / s and the composite material was obtained by equilibrium solidification cooling to room temperature.
[0027] The composite material was found to have a weak CeBi phase impurity peak in addition to the Bi2Te3 phase and the trigonal Te phase. The half-height width of the diffraction peak was very small. The composite material had good crystallinity, no voids on the surface of the material, and an average particle size of 2~10μm. Thermogravimetric analysis found that it had no weight loss below 200℃, and the evaporation amount of Te was about 0.03 wt% at 350℃, and there was no weight loss of Bi. The material was used for thermal evaporation film, and no Bi appeared in the film.
[0028] Example 3 A composite material for high-temperature thermal evaporation of tellurium is prepared from the following raw materials, wherein the raw materials include the following components by mass fraction: tellurium powder (Te): 73%; bismuth particles (Bi): 26%; metal cerium particles (Ce): 0.7%; silicon carbide nanowires: 0.3%. The purity of tellurium powder, bismuth particles and metal cerium particles is 4N, the diameter of silicon carbide nanowires is 25-50nm, and the length is 10-20μm. The preparation method of the composite material is as follows: 1) Weigh the raw materials, mix 130g of bismuth particles, 3.5g of metal cerium particles, 1.5g of silicon carbide nanowires and 328.5g of tellurium powder, place them in a vacuum melting furnace, maintain the vacuum degree at 0.5Pa, and melt at 620℃ for 1h; maintain the solidification rate at 0.05K / s and cool to room temperature for equilibrium solidification to obtain the alloy; the melting adopts programmed temperature increase, first at a rate of 10℃ / min from room temperature to 400℃, and then at a rate of 5℃ / min to 620℃; 2) The alloy was taken out and crushed into 200 mesh to obtain a powder, 36.5 g of tellurium powder was added thereto, and the powder was placed in a vacuum melting furnace, the vacuum degree was maintained at 30 Pa, and the powder was melted at 600 °C for 1.5 h. The melting temperature was programmed, first from room temperature to 400 °C at a rate of 10 °C / min, and then to 600 °C at a rate of 5 °C / min; the solidification rate was maintained at 0.05 K / s and the composite material was obtained by equilibrium solidification cooling to room temperature.
[0029] In addition to the Bi2Te3 phase and the trigonal Te phase, the composite material also has a low-intensity CeBi phase peak, a small half-height width of the diffraction peak, good crystallinity, no voids or cracks on the surface of the material, and an average particle size of 5μm. Thermogravimetric analysis found that there was no weight loss below 200°C, and the evaporation of Te was about 0.05 wt% at 350°C, and there was no weight loss of Bi. The material was used for thermal evaporation film, and no Bi appeared in the film.
[0030] Comparative Example 1 A composite material for high-temperature thermal evaporation of tellurium is prepared from the following raw materials, wherein the raw materials include the following components by mass fraction: tellurium powder (Te): 73%; bismuth particles (Bi): 26%; metal cerium particles (Ce): 0.7%; silicon carbide nanowires: 0.3%. The purity of tellurium powder, bismuth particles and metal cerium particles is 4N, the diameter of silicon carbide nanowires is 25-50nm, and the length is 10-20μm. The preparation method of the composite material is as follows: 1) Weigh the raw materials, mix 130g of bismuth particles, 3.5g of metal cerium particles, 1.5g of silicon carbide nanowires and 365g of tellurium powder, place them in a vacuum melting furnace, maintain the vacuum degree at 0.5Pa, and melt them at 620℃ for 3h; naturally cool them to room temperature under vacuum conditions to obtain an alloy; the melting adopts programmed temperature increase, first from room temperature to 400℃ at a rate of 10℃ / min, and then to 620℃ at a rate of 5℃ / min; 2) The alloy is taken out and crushed into 200 mesh to obtain powder, thereby obtaining a composite material.
[0031] The composite material test found that in addition to the Bi2Te3 phase and the trigonal Te phase, there were also slightly higher intensity impurity peaks, which may be Ce, CeTe, and CeBi related peaks. The half-height width of the main diffraction peaks was small, the composite material had good crystallinity, and the average particle size of the material was 15μm. Thermogravimetric analysis found that there was no weight loss below 200°C, the Te evaporation amount was about 2.3 wt% at 350°C, and the Bi loss was about 0.45wt%. The material was used for thermal evaporation film, and there was no Bi in the film. After the composite material was used for a long time, bismuth could be measured during thermal evaporation, indicating that its long-term stability was poor, there was a certain segregation, and the system stability was poor when the composite material was used as a plating source.
[0032] Comparative Example 2 A composite material for high-temperature thermal evaporation of tellurium is prepared from the following raw materials, wherein the raw materials include the following components by mass fraction: tellurium powder (Te): 74%; bismuth particles (Bi): 26%; the purity of tellurium powder and bismuth particles are both 4N, and the preparation method of the composite material is as follows: 1) Weigh the raw materials, mix 130g of bismuth particles and 333g of tellurium powder, place them in a vacuum melting furnace, maintain the vacuum degree at 0.5Pa, and melt at 620℃ for 1h; maintain the solidification rate at 0.5K / s and cool to room temperature for equilibrium solidification to obtain the alloy; the melting adopts programmed temperature increase, first at a rate of 10℃ / min from room temperature to 400℃, and then at a rate of 5℃ / min to 620℃; 2) The alloy was taken out and crushed into 200 mesh to obtain a powder, 37 g of tellurium powder was added thereto, and the powder was placed in a vacuum melting furnace, the vacuum degree was maintained at 30 Pa, and the powder was melted at 600 °C for 1.5 h. The melting temperature was programmed, first from room temperature to 400 °C at a rate of 10 °C / min, and then to 600 °C at a rate of 5 °C / min; the solidification rate was maintained at 1 K / s and the composite material was obtained by equilibrium solidification cooling to room temperature.
[0033] The composite material test found that there were no other impurity peaks except Bi2Te3 phase and trigonal Te phase, the half-height width of the diffraction peak was small, the composite material had good crystallinity, there were no voids or cracks on the surface of the material, and the average particle size was 13μm. Thermogravimetric analysis found that there was no weight loss below 200°C, the Te evaporation amount was about 1.4 wt% at 350°C, and there was no weight loss of Bi. When the material was used for thermal evaporation film, there was no Bi in the initial film, and a small amount of bismuth appeared in the film after a period of time. The system stability was poor when the composite material was used as a plating source.
[0034] Comparative Example 3 A composite material for high-temperature thermal evaporation of tellurium is prepared from the following raw materials, wherein the raw materials include the following components by mass fraction: tellurium powder (Te): 77%; bismuth particles (Bi): 21%; metal cerium particles (Ce): 1.5%; silicon carbide nanowires: 0.5%. The purity of tellurium powder, bismuth particles and metal cerium particles is 4N, the diameter of silicon carbide nanowires is 5-20nm, and the length is 3-15μm. The preparation method of the composite material is as follows: 1) Weigh the raw materials, mix 100g of bismuth particles, 7.5g of metal cerium particles, 2.5g of silicon carbide nanowires and 300g of tellurium powder, place them in a vacuum melting furnace, maintain the vacuum degree at 10Pa, and melt at 550℃ for 3h; maintain the solidification rate at 5K / s and cool to room temperature for equilibrium solidification to obtain the alloy; the melting adopts programmed temperature increase, first at a rate of 20℃ / min from room temperature to 350℃, and then at a rate of 10℃ / min to 620℃; 2) The alloy was taken out and crushed into 200 mesh to obtain powder, 5 g of bismuth particles and 85 g of tellurium powder were added thereto, and the powder was placed in a vacuum melting furnace, the vacuum degree was maintained at 30 Pa, and the powder was melted at 600 ° C for 5 h with a melting temperature increase rate of 10 ° C / min; then the powder was naturally cooled to room temperature to obtain a composite material.
[0035] The composite material test found that in addition to the Bi2Te3 phase and the trigonal Te phase, there were also weak CeTe, CeBi and BiTe phase peaks. The half-height width of the diffraction peak was slightly wide. The composite material had general crystallinity. There were no voids or cracks on the surface of the material, and the average particle size was 20μm. Thermogravimetric analysis found that Te evaporated about 0.03wt% below 200℃, and about 0.7wt% at 350℃, and Bi lost about 0.02wt%. When the material was used for thermal evaporation, a small amount of Bi impurities appeared in the film.
[0036] Comparative Example 4 A pure tellurium raw material for high-temperature thermal evaporation with a purity of 99.99% was purchased from Nanjing Muke Nano Co., Ltd. The material was used for thermal evaporation to prepare tellurium film. It was found that when the deposition temperature was increased to 150°C or above, the surface of the film became less dense. Analysis showed that this was caused by the low vapor pressure of the Te material. When the deposition temperature was increased to a certain temperature, the Te material was difficult to deposit into a dense film. It can be seen from the test results of the embodiments and comparative examples of the present invention that the embodiment products of the present invention meet the requirements of high-temperature thermal evaporation, and there is basically no evaporation loss of tellurium in the high-temperature degassing stage. The prepared tellurium film is pure phase Te, well crystallized, and no impurities such as bismuth appear. However, when silicon carbide nanowires are not used, high-temperature stability is prone to problems. It can be seen from the embodiments and comparative example 2 that adding an appropriate amount of silicon carbide nanowires to the raw materials significantly improves the thermal stability and long-term performance of the composite material, while ensuring the controllability of tellurium evaporation and the quality of the film. The comparative examples that deviate from the technical solution of the present application have obvious deficiencies in thermal stability, long-term performance or film quality. The above experiments also illustrate that the introduction of a certain amount of cerium can form a stable intermetallic compound with bismuth and tellurium to reduce the activity of Te / Bi, and the introduction of SiC nanowires can refine the grains and inhibit diffusion. The staged smelting and balanced solidification in the preparation method can effectively adjust the crystallization characteristics and reduce defects. The composite material of the present invention can meet the needs of thermal evaporation tellurium film in the industry, and can directly replace the current raw materials without additional process treatment.
[0037] The above is a detailed introduction to a composite material for high-temperature thermal evaporation of tellurium and its preparation method. The above content is a further detailed description of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.
Claims
1. A composite material for high-temperature thermal evaporation of tellurium, obtained by smelting tellurium powder, bismuth particles and metal cerium particles as raw materials, characterized in that: The composite material at least includes a Bi2Te3 phase and a Te-rich phase.
2. The composite material according to claim 1, characterized in that The purity of the tellurium powder, bismuth particles and metal cerium particles is 4N or above.
3. The composite material according to claim 1, characterized in that The raw materials also include silicon carbide nanowires, the diameter of which is 5-50 nm and the length of which is 0.1-20 μm.
4. The composite material according to any one of claims 1 to 3, characterized in that The raw materials include the following components by mass fraction: tellurium powder (Te): 70%~74%; bismuth particles (Bi): 25%~29%; metal cerium particles (Ce): 0.5%~1%; silicon carbide nanowires: 0~0.5%.
5. The composite material according to claim 4, characterized in that The smelting is specifically as follows: weighing raw materials, mixing the weighed bismuth particles, metal cerium particles, silicon carbide nanowires and 90% by weight of tellurium powder, placing the mixture in a vacuum melting furnace, maintaining a vacuum degree of 0.01-100 Pa, and smelting at 620° C. for 0.5-2 hours; then adopting a balanced solidification process, maintaining a solidification rate of 0.05 K / s to room temperature to obtain an alloy; taking out the alloy and crushing it into 100-300 mesh powders, adding the remaining tellurium powder and placing it in a vacuum melting furnace, maintaining a vacuum degree of 0.01-100 Pa, and smelting at 600° C. for 1-2 hours; then adopting a balanced solidification process, maintaining a solidification rate of 0.05 K / s to room temperature to obtain a composite material.
6. The composite material according to claim 5, characterized in that The melting temperature is programmed, specifically: the temperature is increased from room temperature to 400°C at a rate of 10°C / min, and then increased to the target temperature at a rate of 5°C / min.
7. The composite material according to claim 1, characterized in that The composite material consists of a Bi2Te3 phase and a Te-rich phase, and has an average particle size of 1-10 μm.
8. The composite material according to claim 1, characterized in that When the material is used for thermal evaporation, no bismuth evaporates at 350°C and the evaporated amount of tellurium is less than 0.1wt%.
9. A method for preparing a composite material for high-temperature thermal evaporation of tellurium according to any one of claims 1 to 8, wherein the composite material uses raw materials comprising the following components by mass fraction: tellurium powder (Te): 70% to 74%; bismuth particles (Bi): 25% to 29%; metal cerium particles (Ce): 0.5% to 1%; silicon carbide nanowires: 0 to 0.5%, characterized in that: The preparation method comprises the following steps: 1) Weighing raw materials, mixing weighed bismuth particles, metal cerium particles, silicon carbide nanowires and 90% by weight of tellurium powder, placing in a vacuum melting furnace, maintaining a vacuum degree of 0.01-100 Pa, melting at 620° C. for 0.5-2 h; maintaining a solidification rate of 0.05 K / s, and cooling to room temperature for equilibrium solidification to obtain an alloy; 2) The alloy is taken out and crushed into 100-300 mesh to obtain powder, the remaining tellurium powder is added thereto, and the alloy is placed in a vacuum melting furnace, the vacuum degree is maintained at 0.01-100 Pa, and the alloy is melted at 600°C for 1-2 hours; the solidification rate is maintained at 0.05 K / s and the alloy is cooled to room temperature for equilibrium solidification to obtain a composite material.
10. The method for preparing a composite material according to claim 9, characterized in that: The melting temperature is programmed, specifically: the temperature is increased from room temperature to 400°C at a rate of 10°C / min, and then increased to the target temperature at a rate of 5°C / min.
Citation Information
Patent Citations
Bismuth telluride bulk nanometer material and preparation method thereof
CN101597034A
Preparation method of rare earth doped Bi2Te3 based thermoelectric film material
CN101956158A
Preparation method of Ce-doped topological insulator bismuth telluride single crystal film
CN113502534A
Preparation method for improving mechanical property of bismuth telluride-based thermoelectric material
CN115558997A
Bismuth-antimony-tellurium alloy target material and preparation method thereof
CN116516308A